2000
DOI: 10.1002/1096-9861(20000911)425:1<121::aid-cne10>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic innervation of the subthalamic nucleus in the normal state, in MPTP-treated monkeys, and in Parkinson's disease patients

Abstract: The existence of a dopaminergic innervation of the subthalamic nucleus (STN) has been demonstrated in rats but has remained controversial in primates. The aim of the present study was first to demonstrate the existence of a dopaminergic innervation of the STN in monkeys using tracing methods and then to quantify the loss of dopaminergic fibers in the parkinsonian state in monkeys and humans. Following injection of Fluoro-Gold into the STN of a vervet monkey (Cercopithecus aethiops), retrogradely labeled neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 29 publications
1
57
0
1
Order By: Relevance
“…There are direct projections from STN to the cortex (45, 46) and to the thalamus (47). There are also dopaminergic projections from the SNc to STN (48, 49). Thus, dopamine can be seen to influence all glutamatergic synapses within the basal ganglia–thalamo-cortical circuit (Figure 1).…”
Section: Basal Ganglia Circuitrymentioning
confidence: 99%
“…There are direct projections from STN to the cortex (45, 46) and to the thalamus (47). There are also dopaminergic projections from the SNc to STN (48, 49). Thus, dopamine can be seen to influence all glutamatergic synapses within the basal ganglia–thalamo-cortical circuit (Figure 1).…”
Section: Basal Ganglia Circuitrymentioning
confidence: 99%
“…The STN is innervated by dopaminergic axons arising from midbrain dopamine neurons including those in the substantia nigra that are susceptible to degeneration in PD (Hassani et al, 1997; François et al, 2000; Prensa et al, 2000; Cragg et al, 2004). This innervation has, until recently, been overlooked due to its modest nature compared to that found in the striatum.…”
Section: Dopamine In the Stnmentioning
confidence: 99%
“…Anatomical studies have demonstrated that the STN receives sparse collaterals from the nigrostriatal pathway which pass the nucleus at its dorsal surface (Lavoie et al, 1989; Hedreen, 1999; Augood et al, 2000; Francois et al, 2000). These inputs form symmetric synapses on dendrites of STN neurons in rats (Cragg et al, 2004) and monkeys (Smith and Kieval, 2000).…”
Section: Extrastriatal Actions Of Dopaminementioning
confidence: 99%